1985
DOI: 10.1111/j.1365-3180.1985.tb00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of submerged aquatic macrophytes with terbutryne: availance, phytotoxicity and persistence

Abstract: Summary In ideal conditions (static assay with long exposure time) several species of submerged weeds (Myriophyllum propinquum A. Cunn, Potamogeton tricarinatus F. Muell and A. Benn, and Vallisneria gigantea Graebner) were controlled by terbutryne at initial concentrations of <0·2 g m−3. However, since water management practices in irrigation systems limit the contact time which can be imposed, the availance (concentration‐time integral required for effectiveness) was further investigated, using Elodea canaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In natural water bodies, available surfaces such as those of plants, submerged rocks, and so on tend to be covered with Aufwuchs, a heterogeneous layer comprised of periphyton, bacteria, detritus, and associated particulate matter [19,20]. The plant material used in this metabolism study was sampled from an established pond during the spring, when plants have been found to be covered in less Aufwuchs than during the autumn [20]. Nevertheless, a certain amount of Aufwuchs would have been present on the plants, and the enzyme activities of the organisms in this layer may have contributed to the degradation of the [ 14 C]-cyhalothrin on the plant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In natural water bodies, available surfaces such as those of plants, submerged rocks, and so on tend to be covered with Aufwuchs, a heterogeneous layer comprised of periphyton, bacteria, detritus, and associated particulate matter [19,20]. The plant material used in this metabolism study was sampled from an established pond during the spring, when plants have been found to be covered in less Aufwuchs than during the autumn [20]. Nevertheless, a certain amount of Aufwuchs would have been present on the plants, and the enzyme activities of the organisms in this layer may have contributed to the degradation of the [ 14 C]-cyhalothrin on the plant surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In natural water bodies, available surfaces such as those of plants, submerged rocks, and so on tend to be covered with Aufwuchs, a heterogeneous layer comprised of periphyton, bacteria, detritus, and associated particulate matter [19,20]. The plant material used in this metabolism study was sampled from an established pond during the spring, when plants have been found to be covered in less Aufwuchs than during the autumn [20]. Nevertheless, a certain amount of Aufwuchs would have been present on the plants, and the enzyme activities of the organisms in this layer may have contributed to the degradation of the [ 14 C]Λ‐cyhalothrin on the plant surfaces.…”
Section: Discussionmentioning
confidence: 99%